2017
DOI: 10.1007/s00535-017-1360-z
|View full text |Cite
|
Sign up to set email alerts
|

Combinational use of hepatitis B viral antigens predicts responses to nucleos(t)ide analogue/peg-interferon sequential therapy

Abstract: The combinational use of HBsAg and HBcrAg levels at baseline and their changes throughout sequential therapy may be useful for predicting a response to NUC/peg-IFN sequential therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…NAs are excellent drugs for suppressing the replication of HBV, but many patients need to receive long-term treatment. PEG-IFN is a possible therapeutic tool for successfully withdrawing NA treatment in HBV-infected patients, and we participated in two clinical studies on this point in Japan; however, the VR ratios were not high, being around 30% in both [26,27]. We therefore explored new factors associated with the treatment efficacy of PEG-IFN following NA treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NAs are excellent drugs for suppressing the replication of HBV, but many patients need to receive long-term treatment. PEG-IFN is a possible therapeutic tool for successfully withdrawing NA treatment in HBV-infected patients, and we participated in two clinical studies on this point in Japan; however, the VR ratios were not high, being around 30% in both [26,27]. We therefore explored new factors associated with the treatment efficacy of PEG-IFN following NA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We previously participated in two prospective cohort studies regarding PEG-IFN monotherapy following NA treatment [26,27]. As mentioned in a previous study, the analysis of one study arm was considered to include minimal bias [26].…”
Section: Peg-ifn Therapy and Its Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…This might be caused by differences in the included HBV genotypes, as HBV genotypes have specific geographic distributions and can affect the response to IFNα therapy. 22,23 The outcomes of sequential therapy have been unsatisfactory in Japanese studies (including ours), [24][25][26][27][28] at least in part because genotype C is the most prevalent type of HBV, and is associated with a low likelihood of a favorable response to IFNα treatment.…”
Section: H Epatitis B Virus (Hbv) Infection Affects Nearly 250mentioning
confidence: 90%
“…peg-IFN monotherapy was also found to be efficient for HBsAg loss and seroconversion, but combination therapy was thought to cause more adverse events [12][13] . However, other studies have reported that the therapeutic efficacy of NAs combined with peg-IFN was better than monotherapy 14 .NAs are thought to directly inhibit HBV DNA replication, while peg-IFNα-2a as an immunomodulator can enhance the innate and adaptive immune responses to play a synergistic antiviral role 15,16 . In one study 10 , addition of NAs to peg-IFNα-2a therapy enhanced the virologic response in chronic hepatitis B patients who did not have an early response to peg-IFNα-2a.…”
Section: Discussionmentioning
confidence: 99%